AUTOBIOGRAPHY AS THEORY: EMMA GOLDMAN, FREE LOVE, AND THE POLITICS OF NON-BELONGING - Marđonović, Minja (Political Review, 2026)
This paper examines Emma Goldman’s thought through the lens of autobiography as a theoretical and historiographical source, arguing that Living My Life should not be read merely as a record of political activity, but as a primary site of anarcho-feminist knowledge production. Through an analysis of Goldman’s autobiographical writing and theoretical essays, the paper demonstrates that her critique of the state and marriage consistently extends into the sphere of intimacy, where marriage  is  understood as an institutional apparatus that reproduces gender hierarchy and regulates emotional life. In contrast, free love is interpreted not as a private ethical or sexual stance, but as a political practice of non-belonging — an intimate relationship based on voluntariness, non-possessiveness, and the rejection of normative regimes governing personal relationships. The paper argues that Goldman’s autobiographical method destabilizes the conventional divide between the personal and the political, offering a feminist model of situated knowledge in which theory emerges from lived experience, emotion, and resistance. By treating autobiography as both a methodological approach and a political act, this study contributes to contemporary feminist and political theory by highlighting the epistemological significance of life-writing in the formation of radical critiques of authority, intimacy, and freedom.
Keywords: Emma Goldman; free love; anarcho- feminism; autobiography; non-belonging; marriage; intimacy